The Robert Shaw reader - Shaw, Robert, 1916-1999 (Yale University Press, 2004)
Robert Shaw is considered to be the most influential choral conductor in American history. This is the first collection of his letters and notes about music ever published - at another time, it is the book Shaw would have written himself. The letters are an invigorating mix of music history and analysis, philosophy, inspiration, and practical advice. Shaw examines technique, but only as a means to an end; he moves beyond this, delving into the essence of what music is and what it has to say to us. The heart of the book is composed of Shaw's previously unpublished notes on fifteen major choral works, ranging from Bach's B Minor Mass to Stravinsky's Symphony of Psalms. Often inspiring and sometime hilarious, these writings reveal the full breadth of Shaw's knowledge, intensity, and humour.